Assessment of climate change impacts on water balance components of Heeia watershed in A Study on the Wind-Induced Flutter Energy Harvester (WIFEH) Integration into Buildings - Calautit, J.K. (2020)
This study investigates the potential building integration and energy harnessing capabilities of the Wind-Induced Flutter Energy Harvester (WIFEH) – a microgenerator intended to provide energy for low-powered applications. The work presents the experimental investigation of the WIFEH inside a wind tunnel and a case study using Computational Fluid Dynamics (CFD) modelling of a building integrated with a WIFEH system. The experiments examined the WIFEH under various wind tunnel wind speeds varying between 2.3 up to 10 m/s in order to gauge the induced voltage generation capability of the device. This location produced the largest power output under the 45˚ angle of approach, generating an estimated 62.4 mW of power under accelerated wind in device position of up to 6.2 m/s. The method and results presented in this work could be useful for the further investigation of the integration of the WIFEH in the urban environment.